Determinação de energia e metabolizabilidade de nutrientes da farinha de resíduo de camarão em frangos caipiras - Nascimento, Robson Santos (2014)
The objective of the present work was to determine the apparent metabolizable energy (AME) and the coefficients of metabolization of flour shrimp waste (FRC) in broilers rednecks Color Plume (CPK) not sexed, under different methodologies for collecting and ages. In experiment 1 180 birds aged 28 to 40 days subject to the total collection system were used. In experiment 2 150 birds age of 53 to 65 days undergoing total and partial collection of excreta use of acid insoluble ash indicator (CIA) were used. The experimental design was completely randomized with five treatments and six replicates of six five birds each, respectively. Treatments consisted of a basal diet based on corn and soybean meal -four test diets with 5, 10, 15 and 20 % replacement of FRC in the reference diet. The experiment lasted 12 days, seven days of adaptation to the cages and the test diets and 5 days for collection of excreta and quantification of food intake. Until each experimental period the birds were reared in shed masonry, floor covered with wood shavings beaten, which received commercial food and water at will. The samples were collected individually frozen until the end of the trial period, after which you were homogenized and prepared separately for analysis of dry matter (DM), crude protein (CP) and gross energy (GE). FRC was determined for values of 87,4 % DM, 32,6 % PB, 40% MM , 12.1% calcium, 2.3 % phosphorus , and 2385 kcal of gross energy / kg of DM . The average coefficients of metabolizability determined at the age of 28 to 40 days and between 53 to 65 days were respectively, 70,5 and 78,7 % for dry matter and 65,2 to 72,5 % crude protein. The apparent metabolizable energy (AME ) of FRC in particular natural matter in the first stage of establishment was 1092 kcal / kg of DM , and the second phase was 1260 kcal / kg in MN , regardless of the methodology .